Pyrrolizidine alkaloids in food and phytomedicine: Occurrence, exposure, toxicity, mechanisms, and risk assessment - A review. (February 2020) - Schrenk, Dieter; Gao, Lan; Lin, Ge; Mahony, Catherine; Mulder, Patrick P.J.; Peijnenburg, Ad; Pfuhler, Stefan; Rietjens, Ivonne M.C.M.; Rutz, Lukas; Steinhoff, Barbara; These, Anja
Abstract: Among naturally occurring plant constituents, the 1, 2-unsaturated pyrrolizidine alkaloids (in the following termed 'PAs') play a distinct role because of the large number of congeners occurring in nature and the pronounced toxicity of some congeners. Several PAs are hepatotoxic in humans, experimental and farm animals and were shown to be potent hepatocarcinogens in laboratory rodents. Although the general mode of action leading to toxicity has been elucidated, i.e., being mediated by metabolic conversion of the parent molecule into a highly reactive electrophile capable of attacking cellular target molecules, major questions related to the risk assessment of PAs remain unresolved. It was the aim of a workshop held in September 2018 to shed more light on the occurrence, exposure, mode of action, toxicokinetics and –dynamics of PAs to improve the scientific basis for an advanced toxicological risk assessment. The contributions in nine chapters describe the scientific progress using advanced analytical methods, studies in subcellular fractions, cell culture, experimental animals and humans and the use of PBPK modeling and structure-activity relationship considerations aiming at a better understanding of PA toxicity and genotoxicity. Since PAs differ considerably in their toxic potencies and substantial species differences in sensitivity towards PA exposure exist, a special emphasis was placed on these issues.